PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP KINERJA PEGAWAI PADA DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI SUMATERA BARAT - Doni Marlius; Iis Sholihat (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine the effect of the physical and non physical work environment on the performance of Department of Archives and Library of West Sumatra Province. The method used in this research is quantitative research with descriptive approach. The population in this study were employees of Department of Archives and Library of West Sumatra Province amounting to 116 people. The sample used was 116 people using saturated sampling technique. The data analysis technique is multiple linear regression. The results showed that: (1) Physical Environment has a positive and significant effect on Employees Perfomance of Department of Archives and Library of West Sumatra Province, (2) Non-physical Environment has a positive and significant effect on Employees Perfomance of Department of Archives and Library of West Sumatra Province